Desert land reclamation programs and family land dynamics in the Western Desert of the Nile Delta (Egypt), 1960–2010. (April 2018) - Alary, Véronique; Aboul-Naga, Adel; Osman, Mona A.; Daoud, Ibrahim; Abdelraheem, Sahar; Salah, Ehab; Juanes, Xavier; Bonnet, Pascal
Highlights: Life-story approach captures complexity of land dynamics in the livelihood approach. Land reclamation is economically viable for small settlers, but with unequal outcomes. Land dynamics of new settlers escape land policies and generate new rural spaces. Settlers' livelihood activities and strategies vary with their origin and knowledge. Dual-purpose crop-livestock systems contributed to settlers' livelihood security. Abstract: The agricultural development on newly reclaimed lands has led to many national debates about food security and budget deficits, and the living conditions of the new settlers at the local level. This debate is still crucial for present day Egypt, a country facing major challenges, including food security, agriculture modernization, employment generation, and land fragmentation due to dramatic population growth. In this context, policy makers are always seeking the best land allocation system for these new lands. This paper analyzes the land tenure and land use dynamics of farmers' settlements during a program of land reclamation (from 1960 to 2010) in the Western Desert of the Nile Delta. The objective is to describe the land development paths of farm settlement and to identify promising dynamics by cross-referencing the farmers' stories and their livelihood achievements. To accomplish that, we conducted household surveys and interviews to learn the life stories' of 175 family farms. Our study finds that, beyond the rules and institutions that fixed the land tenure regimes and its distribution in these new lands, settlers have found different ways to hold on and secure their land farm, even if the unequal land distribution still structure the population. The results highlight also the dynamism of small-scale settlers, regarding livelihood diversification, to face the challenges of these desert environments. In addition, the dual-purpose system embedded in mixed crop-livestock systems can contribute to settlers' livelihood security. These realities confound the unchanged rhetoric of government and this calls for more social consideration of these new rural spaces based on a combination of heterogeneous networks off relationships and knowledge. The apparent gap between the macro- and micro-perspectives analyses also requires multi-scale assessments. Finally, the life-story method proves to be a complementary and useful approach to integrate the livelihood representation and dynamic.